The Effect of Trust on Gaze-Mediated Attentional Orienting - Barbato, Mariapaola; Almulla, Aisha A.; Marotta, Andrea (Frontiers in Psychology, 2020)
The last two decades have witnessed growing interest in the study of social cognition and its multiple facets, including trust. Interpersonal trust is generally understood as the belief that others are not likely to harm you. When meeting strangers, judgments of trustworthiness are mostly based on fast evaluation of facial appearance, unless information about past behavior is available. In the past decade studies have tried to understand the complex relationship between trust and joint visual attention (i.e. attentional orienting following another person’s gaze). This review will focus on the studies that used a gaze-cueing paradigm to explore this relationship. One study found enhanced gaze-following behavior with trustworthy faces; another one found stronger effects of gaze-following with faces associated with undesirable behavior. Notably, the majority of studies failed to observe significant interactions between trust and gaze-following. Overall, the evidence is mixed, and studies have highlighted the complexity of this relationship. Multiple factors seem to play a role, including the type of manipulation to induce trust, the level of trait-anxiety, and gender. We conclude that further investigation is needed to clarify whether an interaction exists between trust and joint visual attention, possibly focusing on the potential role of perceived threat.